Case Report: Identification of Maternal Low-Level Mosaicism in the Dystrophin Gene by Droplet Digital Polymerase Chain Reaction - Jin, Pengzhen; Gao, Xiaoyang; Wang, Miaomiao; Qian, Yeqing; Yang, Jingjin; Yang, Yanmei; Xu, Yuqing; Xu, Yanfei; Dong, Minyue (Frontiers in Genetics, 2021)
Germline mosaicism should be suspected when the same de novo mutations are identified in a second pregnancy with asymptomatic parents. Our study aims to find a feasible approach to reveal the existence of germline mosaicism. Multiplex Ligation-dependent Probe Amplification was performed on a Duchenne muscular dystrophy affected pedigree to detect deletion mutations. Then gap-polymerase chain reaction was performed to amplify the breakpoints junction sequence. Droplet digital polymerase chain reaction was utilized to identify the mutation frequencies in healthy parents. The same deletion in the exon 51 of the dystrophin gene, which was 50,035 bp in size, was detected in the proband and the fetus but not in their parents. Droplet digital polymerase chain reaction analysis of peripheral blood samples revealed mutant alleles of 3.53% in maternal blood cells. We here report a case of maternal low-level mosaicism confirmed by droplet digital polymerase chain reaction in peripheral blood samples, which reveals the existence of germline mosaicism. Gap-polymerase chain reaction combined with droplet digital polymerase chain reaction provide insights into the detection of germline mosaicism.